An ethics of forgiveness - Vorster, J. M. (Verbum et ecclesia, 2009)
This article investigates the argument that the Christian idea of forgiveness can and should be translated into a socio-political context, from a Reformed perspective. It furthermore endeavours to provide guidelines that can be applied in the sphere of a political transition of the basis of an ethics of forgiveness. The new post-Apartheid society of South Africa is a good example of such a political transition. The central theoretical argument of this investigation is that the Christian theological perspective of forgiveness can indeed be translated into a socio-political praxis. Seen within the context of major biblical themes, this can provide a valuable, if not indispensable, contribution to the quest for reconciliation and nation-building in countries troubled by histories of colonialism, ethnocentrism, tribalism, racism and xenophobia.